2022
DOI: 10.3390/biology11030474
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Yield–Per–Recruit Assessment of the Vulnerable Spiny Lobster Palinurus elephas in the Azores—Implications for Conservation and Fisheries Management

Abstract: The spiny lobster Palinurus elephas has been intensively harvested across its range and is generally considered overfished, with global landings declining sharply from an average of 820 t in 1960–79 to 385 t in 2000–19. Despite its economic and ecological importance, limited information is available to perform stock assessments and make robust management decisions. In this study, demographics and exploitation levels of P. elephas were determined from coastal areas of the Azores, and the relevance of these data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Given the species' high first sale price and moderate mobility, P. elephas has been intensively exploited throughout its range and is today widely considered overfished (Groeneveld et al, 2013). In the Azores, the lobster fishery is still classified as a developing fishery, but recent studies have indicated a worrying situation if stock assessment and management initiatives are not developed (Santos et al, 2022a). It is therefore critical for scientists to provide policymakers with the best available information since effective management is more likely when decision-makers are properly informed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the species' high first sale price and moderate mobility, P. elephas has been intensively exploited throughout its range and is today widely considered overfished (Groeneveld et al, 2013). In the Azores, the lobster fishery is still classified as a developing fishery, but recent studies have indicated a worrying situation if stock assessment and management initiatives are not developed (Santos et al, 2022a). It is therefore critical for scientists to provide policymakers with the best available information since effective management is more likely when decision-makers are properly informed.…”
Section: Discussionmentioning
confidence: 99%
“…LPUE and CPUE were estimated for P. phycis , C. conger , S. latus , S. colias , S. cretense , S. atricauda , L. forbesii , P. pagrus , S. scrofa , P. kuhlii , T. picturatus , Seriola spp., P. elephas , B. splendens , B. decadactylus and A. carbo as kg landing −1 vessel −1 and kg day at sea −1 vessel −1 , respectively. To reduce the influence of potential drivers ( e.g ., targeted species, vessel size, fishing gear) on these catch rates, generalized linear models (GLMs) were utilized to calculate standardized abundance indices (Santos et al ., 2022b). The explanatory factors included in the analysis differed across the different datasets and are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the European market, it can be sold for prices ranging between EUR 40 and EUR 120 per kg [ 28 ]. However, as a general trend, in the second half of the 20th century, P. elephas populations faced a severe decline of its biomass at sea [ 15 , 29 ], due to the excessive fishing that had depleted its populations [ 29 ]. For this reason, the species is assessed as “vulnerable” by the International Union for Conservation of Nature [ 30 ].…”
Section: Introductionmentioning
confidence: 99%